PENERAPAN MODEL INKUIRI BERBANTUAN MEDIA KOMPUTER TERHADAP MINAT BELAJAR KIMIA SMA NEGERI 4 PADANGSIDIMPUAN - Rizky Ariaji; Dakkal Harahap; Sahlan Tuah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
The type of research used in this study is a research experiment. The population in this research is the grade XI IPA SMA Negeri 4 Padangsidimpuan. Instruments used for data collection is a test of interest in learning chemistry in the form of essays and learning interest of students now. The test results obtained (1) there is a change of interest in learning chemistry being taught through the model of learning computer-assisted inkuiri media on the subject of reaction rates on the now interest the average experimental class students which of the 28 students There are 5 students or 18% interest rate which is at a "very good" category, 18 students or 64% in the category of "good", 5 students 18% in the category of "enough". On the control class's interest now is obtained that the average value of the interest of students which of the 28 students there was 1 person or 4% of the students that the level of interest in being on the category "very good", 10 students or 36% on the "good" category, 16 students or 57% in "enough" category, and 1 person or 4% in the category of "less". So the conclusion drawn interest studied chemistry is taught through the model of computer-aided media learning inkuiri higher than on cooperative learning methods. Keywords: Model Inkuiri, Computer Media, Interest In Learning Chemistry.